Comparative study on internal and external determinants of non-performing loans of Islamic banks in Malaysia / Nurul Nazwa Zainal - Zainal, Nurul Nazwa (2016)
This research paper is purposely conducted to identify the determinants of non performing financing of Islamic banks in Malaysia using internal and external variables. Internal variables selected in this study are loan growth, loans to deposit ratio, banks' size and financing contract. While the external factors are GDP annual growth, inflation, interest rate and unemployment rate. This study employs a panel data method using 16 Islamic banks in Malaysia with studies period from 2008 to 2014. This study used secondary data sources and all the variables used are regressed using Ordinary Least Square method in Eviews software. In general, the result found that internal variables are more dominants in determining the NPF of Islamic banks in Malaysia. Based on empirical findings, it is found that loan growth and financing contract are the internal variables that significant in determining the NPF while inflation and unemployment rate are the external factors that significant in determining the NPF of Islamic banks in Malaysia.